Sexy Feminisms & Sexual Health: Theorizing Heterosex, Pleasure, and Constraint in Public Health Research - Higgins, Jenny (Atlantis, 2007)
After outlining the "pleasure deficit" in public health research on family planning, this article applies feminist theorizations of heterosex to study contraceptive use and sexual pleasure. The author considers the limitations and potentials of theorizing heterosex variously as agential, transgressive, and/or constrained for public health research.